Vegetation History and Cultural Landscapes Case Studies from South-west Slovakia - Fehér, Alexander (Springer Geography,, 2018)
This book focuses on the vegetation history of the cultural landscape in southwestern Slovakia, which was established and adopted by mankind and has since constantly evolved in response to ongoing changes (in environmental conditions, biodiversity, land use, etc.). The book analyses four dominant ecosystems typical for the cultural landscape and affected by humans: woodlands, wetlands, grasslands and agricultural land. Each ecosystem is discussed in separate chapters. The chapters include (a) basic information, general aspects, development processes, trends and interpretations, (b) a published or non-published case study based on the author's own research, and (c) an extensive bibliography. A set of maps on the vegetation history and indices of geographical names and plants names serve to round out the coverage. The work provides an essential point of departure for describing the typical regional characteristics of the cultural landscape, with an eye to its future preservation.